Assessment of iron bioavailability from different bread making processes using an in vitro intestinal cell model. (1st August 2017) - Rodriguez-Ramiro, I.; Brearley, C.A.; Bruggraber, S.F.A.; Perfecto, A.; Shewry, P.; Fairweather-Tait, S.
Highlights: Fe availability in three commercial bread baking process was compared. The sourdough bread baking process fully degraded phytic acid, a main Fe chelator. More Fe was released by simulated digestion from sourdough bread. The highest Fe uptake was achieved with sourdough bread in a simulated mixed-meal. The sourdough bread process could be more beneficial for iron nutrition. Abstract: Myo-inositol hexa kis phosphate (IP6), is the main iron chelator in cereals and bread. The aim of this study was to investigate the effect of three commercial baking processes (sourdough, conventional yeast and Chorleywood Bread Making Process (CBP)) on the IP6 content of wholemeal bread, its impact on iron uptake in Caco-2 cells and the predicted bioavailability of iron from these breads with added iron, simulating a mixed-meal. The sourdough process fully degraded IP6 whilst the CBP and conventional processes reduced it by 75% compared with wholemeal flour. The iron released in solution after a simulated digestion was 8-fold higher in sourdough bread than with others but no difference in cellular iron uptake was observed. Additionally, when iron was added to the different breads digestions only sourdough bread elicited a significant ferritin response in Caco-2 cells (4.8-fold compared to the other breads) suggesting that sourdough bread could contribute towards improved iron nutrition.